Utilizing Gene Tree Variation to Identify Candidate Effector Genes in Zymoseptoria tritici - McDonald, M.; McGinness, L.; Hane, James; Willams, A.; Milgate, A.; Solomon, P. (2016)
Zymoseptoria tritici is a host-specific, necrotrophic pathogen of wheat. Infection by Z. tritici is characterized by its extended latent period, which typically lasts two weeks, and is followed by extensive host cell death and rapid proliferation of fungal biomass. This work characterizes the level of genomic variation in 13 isolates for which we have measured virulence on 11 wheat cultivars with differential resistance genes. Between the reference isolate, IPO323, and the 13 Australian isolates we identified over 800,000 single nucleotide polymorphisms, of which ~10% had an effect on the coding regions of the genome. Furthermore we identified over 1700 probable presence/absence polymorphisms in genes across the Australian isolates using de novo assembly. Finally, we developed a gene tree sorting method that quickly identifies groups of isolates within a single gene alignment whose sequence haplotypes correspond with virulence scores on a single wheat cultivar. Using this method we have identified <100 candidate effector genes whose gene sequence correlates with virulence towards a wheat cultivar carrying a major resistance gene.